Gall-Inducing Tephritid Flies (Diptera: Tephritidae): Evolution and Host–Plant Relations - Korneyev, Valery A. (Frontiers in Ecology and Evolution, 2021)
The molecular-based phylogenetic analysis of the subfamily Tephritinae, the subfamily which contains almost all the cecidogenous species of the family Tephritidae, has reassigned several tribes and groups of genera and modified their concepts based on morphology alone to other tribes and thus changed the hypothetical scenarios of evolution of fly / host-plant relations and, in particular, the gall induction in different phylogenetic lineages. Gall induction is shown to arise independently within the Myopitini (in three lineages), Cecidocharini, Tomoplagia group of genera, Eurostini, Eutreta, Tephritis group of genera, Platensinini, Campiglossa group of genera and Sphenella group of genera. Further, gall induction has arisen more or less synchronously, owing to shifts to host plants with smaller flower heads and sensitive to larval feeding causing tissue proliferation. This was possibly a result of temporary aridisation of the grassy biomes in the Nearctic and Afrotropical Regions in the late Miocene or early Pliocene.